2011
DOI: 10.1038/jidsymp.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular and Neuroimmune Aspects in the Pathophysiology of Rosacea

Abstract: Rosacea is a common skin disease with a high impact on quality of life. Characterized by erythema, edema, burning pain, immune infiltration, and facial skin fibrosis, rosacea has all the characteristics of neurogenic inflammation, a condition induced by sensory nerves via antidromically released neuromediators. To investigate the hypothesis of a central role of neural interactions in the pathophysiology, we analyzed molecular and morphological characteristics in the different subtypes of rosacea by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
264
1
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(293 citation statements)
references
References 46 publications
8
264
1
20
Order By: Relevance
“…These forms of cathelicidin peptides are known for its role in natural host defense against infections and in promoting leukocyte chemotaxis, angiogenesis, and extracellular matrix component expression (27) . Supporting this theory, gene array studies found that mRNA expression levels of cathelicidin were found to be significantly increased in all subtypes of rosacea (29) . Additionally, local proteases (serine protease KLK5) that control the production of cathelicidin in epidermis were also abnormally expressed in rosacea patients (25,27) .…”
Section: Etiology and Pathophysiologymentioning
confidence: 62%
See 2 more Smart Citations
“…These forms of cathelicidin peptides are known for its role in natural host defense against infections and in promoting leukocyte chemotaxis, angiogenesis, and extracellular matrix component expression (27) . Supporting this theory, gene array studies found that mRNA expression levels of cathelicidin were found to be significantly increased in all subtypes of rosacea (29) . Additionally, local proteases (serine protease KLK5) that control the production of cathelicidin in epidermis were also abnormally expressed in rosacea patients (25,27) .…”
Section: Etiology and Pathophysiologymentioning
confidence: 62%
“…Studies have demonstrated increased blood flow in the face and larger and more numerous vessels in the face than in other areas of the body (31) . Significantly dilated blood and lymphatic vessels were reported in all subtypes of rosacea (29) . Studies further demonstrated an up-regulation of genes involved in vasoregulation and neurogenic inflammation and suggested that dysregulation of mediators and receptors implicated in neurovascular and neuroimmune communication may be crucial at early stages of rosacea (26,29,32) .…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly dilated blood vessels have been reported in all subtypes of rosacea. 9 • Neurovascular component-this has been suggested to be an underlying mechanism on the basis of exaggerated skin sensitivity to noxious heat stimuli, which may be seen in these patients. 10 DOI: https://doi.org/10.17925/USOR.2017.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[30][31][32][33][34] As a result, many of the studies of therapies used to treat rosacea (eg tetracyclines, azelaic acid, ivermectin) especially with presence of papulopustular lesions, appear to affect inflammatory pathways/modes of action unrelated to an underlying bacterial trigger that appear to be operative in rosacea pathophysiology (eg inhibition of matrix metalloproteinases, downregulation of cathelicidin pathway, reduction in number of Demodex mites). [35][36][37][38][39][40][41][42][43] The large body of evidence supporting an inflammatory pathogenesis of rosacea that is not triggered by a bacterial etiology has led globally to rosacea management recommendations supporting that avoidance of an antibiotic effect whenever possible is favorable in order to reduce the emergence of antibiotic-resistant bacteria.…”
Section: -29 (3) Management Of Rosacea Does Not Require An Antibiotmentioning
confidence: 99%